WAGADHEWE: MEDIA INOVASI SOSIALISASI PENDIDIKAN KARAKTER KAUM MARGINAL BANTARAN SUNGAI BENGAWAN SOLO - Sudaryanto, Memet; Murni, Endri Sintiana; Nurriyah, Nitta Ayu Azzahra Syafa’atun (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Wagadhewe (Wayang Gawean Dhewe) comes as a new breakthrough socialization as well as character development of students who will be directly applied in society. Expected outcomes of this program is a child care Bengawan Solo river bank for the betterment of the moral and spiritual qualities, the founding PABLO (Paguyuban Anak Bengawan Solo) is an interactive, productive, conducive, applicative.. The method used to conduct training with thirty four observation times and one time gig, plus two times the training of marriage conductivity, formed a partnership with local RT, ketua RW as coordinator of entrepreneurship and a team of expert consultants, Rumah Hebat Indonesia.The Results is the creation Wagadhewe with more than 45 types, workshop passes are able to express themselves, character creation stories are inspiring and sometimes unthinkable by adults.